2010
DOI: 10.1016/j.resp.2010.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Role of central neurotransmission and chemoreception on airway control

Abstract: This review summarizes work on central neurotransmission, chemoreception and CNS control of cholinergic outflow to the airways. First, we describe the neural transmission of bronchoconstrictive signals from airway afferents to the airway-related vagal preganglionic neurons (AVPNs) via the nucleus of the solitary tract (nTS) and, second, we characterize evidence for a modulatory effect of excitatory glutamatergic, and inhibitory GABAergic, noradrenergic and serotonergic pathways on AVPN output. Excitatory signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 123 publications
(209 reference statements)
1
15
0
1
Order By: Relevance
“…NTS neurons send direct projections to the vagal preganglionic neurons in the rostral nucleus ambiguus. These neurons, in turn, project to the intrinsic tracheobronchial ganglia, which provide the innervation to airway smooth muscle, submucosal glands and the vasculature (reviewed in Kc and Martin, 2010). Several tract tracing studies have demonstrated that NTS neurons also send monosynaptic projections to the ventral respiratory group (Alheid et al, 2011; Ellenberger and Feldman, 1990; Rosin et al, 2006).…”
Section: Role Of Vagal Neurocircuitry In Nausea and Vomitingmentioning
confidence: 99%
“…NTS neurons send direct projections to the vagal preganglionic neurons in the rostral nucleus ambiguus. These neurons, in turn, project to the intrinsic tracheobronchial ganglia, which provide the innervation to airway smooth muscle, submucosal glands and the vasculature (reviewed in Kc and Martin, 2010). Several tract tracing studies have demonstrated that NTS neurons also send monosynaptic projections to the ventral respiratory group (Alheid et al, 2011; Ellenberger and Feldman, 1990; Rosin et al, 2006).…”
Section: Role Of Vagal Neurocircuitry In Nausea and Vomitingmentioning
confidence: 99%
“…Design for reflex protection of the airway via bidirectional central nervous system (CNS)-airway pathways, repeated exposures to environmental pollutants, inflammatory stimuli, and other noxious agents may modulate afferent airway sensory pathways (150,315,316), leading to increased excitability of airway-related vagal preganglionic neurons and airway hyperresponsiveness. The extensive and exquisite neural control of airways has been previously reviewed (150,177,317,318). CNS control of the airway involves integrated netReview L920 NOVEL ROLES OF AIRWAY SMOOTH MUSCLE works along the central neural axis, particularly the vagal preganglionic neurons within the medulla, which form the final common pathway from the brain to the airways.…”
Section: Neural Controlmentioning
confidence: 99%
“…Nevertheless, insulin regulates hepatic glucose production by activating parasympathetic pre-ganglionic fibers from dorsal vagal complex (DVC) at the brainstem [86], located at the vicinity of the nucleus ambiguus (NA), which in turn innervate the airways. Vagal preganglionic neurons that innervate the airways arise primarily from the rostral NA (rNA) and to a lesser degree from the rostral portion of the dorsal motor nucleus of the vagus [87]. It is plausible that insulin may also regulate bronchial contractile responses by modulating the vagal tonus that originates from these nucleuses (Fig.…”
Section: Insulin and Airway Smooth Muscle (Asm) Hyperresponsivenessmentioning
confidence: 99%